2018
DOI: 10.3390/antiox7080096
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Omega-Polyunsaturated Fatty Acids and Their Oxidized Products in Salmon after Different Cooking Methods

Abstract: Consumption of food containing n-3 PUFAs, namely EPA and DHA, are known to benefit health and protect against chronic diseases. Both are richly found in marine-based food such as fatty fish and seafood that are commonly cooked prior to consumption. However, the elevated temperature during cooking potentially degrades the EPA and DHA through oxidation. To understand the changes during different cooking methods, lipid profiles of raw, boiled, pan-fried and baked salmon were determined by LC-MS/MS. Our results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 39 publications
1
53
0
Order By: Relevance
“…Previous studies have shown that the animals fed with dietary fat and oils increased lipid peroxidation as measured by elevated blood MDA concentrations [57] . In addition to endogenous lipid peroxidation, the MDA content in food was significantly increased after pan- or deep-frying [58] because of the oxidation of polyunsaturated fatty acids, and the ingested MDA could be taken up and subsequently excreted [59] . Based on the above previous studies, a lower urinary MDA concentration in MV patients may be because MV patients receive a modified diet via enteral feeding, which does not contain fried food, and hence MDA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the animals fed with dietary fat and oils increased lipid peroxidation as measured by elevated blood MDA concentrations [57] . In addition to endogenous lipid peroxidation, the MDA content in food was significantly increased after pan- or deep-frying [58] because of the oxidation of polyunsaturated fatty acids, and the ingested MDA could be taken up and subsequently excreted [59] . Based on the above previous studies, a lower urinary MDA concentration in MV patients may be because MV patients receive a modified diet via enteral feeding, which does not contain fried food, and hence MDA.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of DHA and EPA 7.67% and 0.65%, respectively, raw fish fillet and 0.87 and 0.20% found in fried fish fillet respectively, this shows the frying activity reduces the content of both DHA and EPA in fish fillet, and specially, a pronounced reduction was observed in DHA by frying practice. The other researchers did confirm as frying decreases EPA and DHA in all frying treatments independent of the fat used depends most probably on the fact that these fatty acids were not present in the frying fats (Gladyshev et al, 2007;Leung et al, 2018;Sampels et al, 2014).…”
Section: Ta B L Ementioning
confidence: 93%
“…(ALA), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA), are important to human health, as they have been reported to protect against cardiovascular disease and neurodegeneration and to reduce inflammation (Leung, Galano, Durand, & Lee, 2018). Besides playing important role in cardiovascular and inflammatory diseases, the essential fatty acids are vital in the development of neuron in infants and in fat glycolic control.…”
mentioning
confidence: 99%
“…The oil used in one study was not rich in ω‐3 FA (Seppanen & Csallany, ). Different matrices and heating methods were used in another study (Leung et al ., ), and oil was not heated to temperatures exceeding 37 °C (Viau et al ., ). Another important difference between those studies and ours was heating time, as our heating experiment was much longer.…”
Section: Resultsmentioning
confidence: 99%